Capital Structure, Firm Size, and Firm Growth: Do They Influence Firm Value Through Profitability? Evidence from Indonesian Manufacturing Firms - Hindasah, Lela; Suprijanto, Dewi Hasanah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Firm value represents an important indicator of corporate performance and reflects investors’ perceptions of a company’s future prospects. Understanding the factors that influence firm value is therefore crucial for both managers and investors. This study aims to examine the effects of capital structure, firm size, and firm growth on firm value, with profitability acting as a mediating variable. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Using a quantitative research approach, secondary data were collected from companies’ financial statements, resulting in 433 firm-year observations selected through purposive sampling. Panel data regression analysis was employed to examine the direct relationships among variables, while the Sobel test was used to analyze the mediating role of profitability. The results show that capital structure has a negative and significant effect on profitability, whereas firm size and firm growth have positive and significant effects on profitability. However, capital structure, firm size, and firm growth do not have significant direct effects on firm value. Profitability, on the other hand, has a positive and significant influence on firm value. Furthermore, the mediation analysis confirms that profitability significantly mediates the relationships between capital structure, firm size, firm growth, and firm value. These findings suggest that profitability plays a crucial role in transmitting the effects of corporate financial and operational characteristics on firm value. Therefore, companies seeking to enhance their market value should prioritize strategies that improve financial performance and profitability.